Faktor-Faktor yang Mempengaruhi Kualitas Hidup pada Pasien Kanker Serviks: Literatur Review - Merida Simanjuntak (AKPER Pasar Rebo, 2021)
Cervical cancer is one of the most successfully treated forms of cancer, provided it is detected early and managed effectively. Cancers diagnosed at a late stage can also be controlled with proper treatment and palliative care. The study aims to review the relationship between nursing interventions in improving quality of life in patients with cervical cancer. Method: Literature Review refers to the issues, methodologies and equations of the results and methods used. There are 5 articles used in the review literature. Data searches are conducted in international and national journals. The results showed that treatment interventions were very influential in improving the quality of life of cancer patients. The support group approach is considered effective in improving the quality of life of patients with cervical cancer.